Pemanfaatan Information and Communication Technology bagi Pengembangan Guru Madrasah Sub Urban - M. Chodzirin (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
The seriousness of the school/madrasah in updating instructional media hampered by the incompetence of some teachers use ICT-based learning media as one way of presenting the material. Mastery and knowledge of information technology will facilitate the teacher in finding the source of learning, so that students will not get bored attend classes. ICT training has been able to change mindside teacher of the conventional learning becomes more interactive learning. Teachers are becoming more aware that the presence of technology is inevitable in the learning process. Rapid technological developments should be exploited so that teachers who emerges is a positive impact, and not vice versa. The use of technology can help the learning process becomes more effective and efficient, and fun.